Mixed biopolymer systems based on starch - Saeed, Mohamed Abd Elgadir Mohamed; Akanda, Md. Jahurul Haque; Ferdosh, Sahena; Amid, Mehrnoush; Alias, Abd Karim; Noda, Takahiro; Sarker, Md. Zaidul Islam (MDPI, 2012)
A binary mixture of starch–starch or starch with other biopolymers such as protein and non-starch polysaccharides could provide a new approach in producing starch-based food products. In the context of food processing, a specific adjustment in the rheological properties plays an important role in regulating production processing and optimizing the applicability, stability, and sensory of the final food products. This review examines various biopolymer mixtures based on starch and the influence of their interaction on physicochemical and rheological properties of the starch-based foods. It is evident that the physicochemical and rheological characteristics of the biopolymers mixture are highly dependent on the type of starch and other biopolymers that make them up mixing ratios, mixing procedure and presence of other food ingredients in the mixture. Understanding these properties will lead to improve the formulation of starch–based foods and minimize the need to resort to chemically modified starch.